Do Multinational Enterprises Relocate Employment to Low Wage Regions? Evidence from European Multinationals - Jozef Konings; Alan Patrick Murphy (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 2003)
This paper analyzes the employment behavior of home multinational enterprises (MNEs) in Europe. To this end we use a unique firm level panel data set of more than 1,000 European multinational parent enterprises and their affiliates. The affiliates are located either in the European Union (North, South), Central and Eastern Europe or both. We find for parent firms operating in the manufacturing sector that the labor cost elasticity of parent employment with respect to North EU affiliates?labor costs is positive and statistically significant, ranging from 0.03 to 0.08, depending on the specification considered. This implies employment substitution between parents and their North EU based affiliates takes place in response to wage cost differentials between the parent and its North EU based affiliates. This substitution effect becomes stronger when affiliates are operating in a different sector than their parent firm. However, we find no evidence for such substitution effects between parent employment and its affiliates that are located in low wage regions in the EU and in Central and Eastern Europe. Furthfirmore substitution effects are absent for parent firms operating in the nonmanufacturing sector. Our results suggest that on average the competition from low wage countries in Central and Eastern Europe and the South of the EU did not contribute to a relocation of domestic jobs to these low wage regions.
Keywords: F23; J23; 330; Key words: Relocation; Multinational Enterprises; Labor Demand; Betriebliche Standortwahl; Multinationales Unternehmen; Lohnniveau; Niedriglohn; EU-Staaten; Osteuropa